The Antibacterial Activity of Acanthus ilicifolius L. n-Hexane Fraction - warsinah, warsinah; Wijaya, Triyadi Hendra; Ekowati, Nuraeni (Journal of Science and Technology Research for Pharmacy, 2022)
Background: Recently, with the high prevalence of diarrhoea caused by bacterial infection, the usage of antibiotics has increased. Antibiotic overuse might lead to several side effects and resistance, suggesting the development of an alternate antibacterial agent. A mangrove plant, Acanthus Illinois, contained triterpenoid, which has antibacterial properties. Aim: This study aimed to evaluate the antibacterial effect of the Acanthus Illinois n-hexane fraction against Escherichia coli and Shigella dysenteriae. Method: The Acanthus Illinois was fraction using n-Hexane, identification of secondary metabolite compound using GC-MS, and evaluation of antibacterial activity against Escherichia coli and Shigella dysenteriae under paper disc methods. This study was designed using a fully randomized design (CRD) with concentrations of fractions 1%, 2%, and 4%. The GC-MS results were compared to the WILEY 9 library and analysed. A prism graph was used to measure the inhibition zone of antibacterial activity. Result: The n-hexane fraction yield is 3.3% and contains sesquiterpene compounds (trans (beta.)-caryophyllene, alpha humulene, naphthalene decahedron-4A-methyl), terpenoid alcohol (3,7,11,15-tetramethyl -2-hexadecane-1-ol), and fatty acids (hexadecanoic acid methyl ester. Acanthus Illinois n-hexane fraction has antibacterial activity against Escherichia coli and Shigella dysenteriae in a dose-dependent manner. Conclusion: The n-hexane fraction of leaves Acanthus ilicifolius contains sesquiterpene, alcohol terpenoids, and fatty, and has antibacterial activity against Escherichia coli and Shigella dysenteriae